Pengalaman Mahasiswa Dalam Menghadapi Seksisme Di Lingkungan Organisasi - Kartika Dewanti; Riza Ayu Lestari; Elfrida Hotmauli Sitorus; Gina Aprillia; Kariza Rossa Juliana (Advances In Education Journal, 2025)
The purpose of this study is to learn about the experiences of students who encounter sexism in student groups and to develop preventative and remedial measures. As informal educational settings, student organizations are perfect for fostering social awareness, networking, and leadership skills. Reality, however, demonstrates that sexism still poses a serious obstacle, particularly for female students and those who exhibit non-conforming gender characteristics. Through in-depth interviews with students who are involved in organizations and have firsthand experience with sexism, this study combined a qualitative technique with a phenomenological method. Purposive sampling was used to choose participants in order to guarantee a range of backgrounds. Phenomenological reduction was used to examine the data, which included organizing, analyzing, and determining the main themes of the experiences of the participants. Triangulation was used to test their validity. According to the findings, students encountered sexism in the form of verbal harassment based on gender, unfavorable stereotypes, male dominance in decision-making, discrimination in leadership positions, and degrading remarks. In addition to limiting opportunities for active engagement and expression, the ensuing effects included psychological pressure that lowered the caliber of students' contributions. The introduction of a zero-tolerance policy against sexism, anti-discrimination communication training, gender awareness education, and the creation of a safe reporting channel through the PPKS Task Force are among the prevention tactics that have been identified. In order to establish a campus environment that is safe, equal, and free from discrimination, this study highlights the significance of changing an organizational culture that is inclusive and gender-responsive, encompassing the entire academic community.